Intergenerational obesity profiling in Malaysia and exploration of mother-child obesity determinants among Malay low socioeconomic individuals: a mixed method study - Mohamed, Nur Nadia (2023)
Maternal and child overweight or obesity (OW/OB) has become a public health concern because it can lead to a continuous intergenerational OW/OB. Besides genetic inheritance, OW/OB among mothers and children are also influenced by personal and environmental factors. This study aimed to describe the prevalence trends and factors associated with OW/OB among mothers and their children. Moreover, this study also seeks to explore how intergenerational OW/OB occurs in low-income households. A convergent mixed methods design was applied, combining quantitative data obtained from the Malaysian National Health and Morbidity Survey and the findings from the qualitative study. The quantitative and qualitative studies data were collected and analysed independently in a single phase. In the quantitative study, a mother and a child aged between 5 to 17 years were identified from every household, and they were matched as mother-child pairs according to their body mass index categories. The prevalence and associated factors of overweight mother/overweight child pairs (OWM/OWC) were analysed for the years 2006, 2011, and 2015. Multiple logistic regressions analysis was performed to determine the factors associated with OWM/OWC. In the qualitative study, maternal perception of how they and their children become overweight or obese was explored through in-depth interviews. A total of 27 in-depth interviews were carried out. A thematic analysis approach was used to analyse the qualitative data. Data obtained from both studies were integrated through a narrative approach. Between the years 2006 to 2015, the prevalence of OWM/OWC increased from 15.3% to 21.7%. Surprisingly, the prevalence of OWM/OWC in the lowest income group doubled from 7.9% to 17.8% over the same period. The risk of OWM/OWC increased as maternal age increased. Among children, aged between 10 to 14 years had a higher risk of OWM/OWC, while aged between 15 to 17 years were protective against OWM/OWC. The risk of OWM/OWC also elevated among mothers with primary and secondary education levels. Meanwhile, being Chinese, Other ethnicity, and large household size were protective against OWM/OWC. In qualitative study, 27 Malay women aged between 27 to 52 years were interviewed. Four major themes emerged from in-depth interviews. First, personal factors can influence intergenerational OW/OB through demographic, cognitions, and skills. The second theme was the social environment of parent-child relationships. The third theme was the physical environment, which comprises the home and built environments. The final theme was the macro-level environment, including food price and media influence. In conclusion, the prevalence of OWM/OWC in this country is on the rise, particularly in low-income households. Besides personal factors, the social, physical and macro-level environments are also involved in intergenerational OW/OB.